2000
DOI: 10.1002/1097-4636(200009)53:5<449::aid-jbm2>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying toxic degradation products in cellulose acetate dialyzers

Abstract: In September 1996, seven patients at Hospital A suffered conjunctivitis, hearing loss, diminished vision, and headaches 7-24 h after hemodialysis treatment. Eleven-year-old dialysis modules were identified as a common link between these patients. Degradation of the cellulose acetate (CA) material was identified as the cause of this incident. Degradation products were characterized from retrieved CA dialysis membranes. A series of synthesized CA degradation products was tested in vitro to assess toxicity. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A recent in vivo study with CA oligomers from 13-year-oldfiber component extracts also found PMN activation and onset of some clinical inflammatory symptoms in injected rabbits. 42 This trend toward increased cellular damage and programmed cell death with the older fibers was also noted in the apoptosis data.…”
Section: Discussionmentioning
confidence: 99%
“…A recent in vivo study with CA oligomers from 13-year-oldfiber component extracts also found PMN activation and onset of some clinical inflammatory symptoms in injected rabbits. 42 This trend toward increased cellular damage and programmed cell death with the older fibers was also noted in the apoptosis data.…”
Section: Discussionmentioning
confidence: 99%
“…448 This stress may contribute to premature failure. 463 The dialyzers involved in these tragic events were 13 years old and they were found to have degraded by deacetylation. 454 In polyethylene, the OIT is reduced only slightly but in polypropylene the OIT reduction is large.…”
Section: Medical Equipment and Suppliesmentioning
confidence: 99%